DENTIFICATION OF MATERNAL FACTORS AND NUTRITIONAL STATUS ON THE RISK OF GROWTH AND DEVELOPMENT DISORDERS OF TODDLERS IN THE WORKING AREA OF THE SEKUPANG HEALTH CENTER IN 2026 - Mastiur Lumban Tobing; Netti Brahmana (Yayasan Nuraini Ibrahim Mandiri, 2026)
This study aimed to identify the relationship between maternal knowledge, maternal attitudes, maternal educational level, and toddlers’ nutritional status with the risk of growth and developmental disorders among toddlers in the working area of the Sekupang Health Center, Batam City, in 2026. The study employed an analytical observational design with a cross-sectional approach involving 40 mother–toddler pairs selected using an accidental sampling technique. Primary data were collected through structured questionnaires, anthropometric measurements, and child health records. Data were analyzed using univariate analysis to describe respondent characteristics and Chi-square tests to examine the relationships between the independent and dependent variables at a significance level of 0.05. The results showed that most mothers had a moderate level of knowledge (75%), negative attitudes toward child growth and development (60%), elementary or senior high school educational backgrounds (35% each), and most toddlers had normal nutritional status (67.5%). Bivariate analysis indicated that maternal knowledge (p = 0.012), maternal attitude (p = 0.010), maternal educational level (p = 0.018), and toddlers’ nutritional status (p = 0.025) were significantly associated with the risk of growth and developmental disorders among toddlers. In conclusion, maternal factors and toddlers’ nutritional status are important determinants of the risk of growth and developmental disorders, highlighting the need to strengthen maternal health education, improve positive parenting attitudes, and optimize nutritional interventions through primary health care services to support optimal child growth and development.